PENDUGAAN POTENSI PEREKRUTAN PERMUDAAN ALAM OLEH POHON INDUK DI HUTAN MANGROVE IUPHHK-HA PT. BUMWI, TELUK BINTUNI, PAPUA BARAT Potential Estimation of Seedling Recruitment by Seed Trees in Mangrove Forest IUPHHKHA PT. BUMWI Bintuni Bay, West Papua - Istomo .; Mia Afriyani (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
Since 1978 one of the legal silviculture systems in Indonesian regard to managing mangrove forest is seed tree method. The ability of this silviculture system to recruit the seeds to fulfill the regeneration is one of the importantaspects. The research is conducted to get the information about regeneration condition and the ability of seed tree method to recruit the regeneration in any various plot with different agecutting. Vegetation analysis for naturalregeneration (seedlings and saplings) were conducted at four different age logged-over area with the total 640 plots. The plot size is 78.5 m2. The result showed that existence of seed tree can affect the type of regeneration for seedlings recruitment with percentage between 59.52% to 83.37%.Key words: mangrove, natural regeneration, seed tree, seedling recruitment